2015
DOI: 10.33607/bjshs.v3i98.90
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Muscle Strength of Dominant and Non-Dominant Ankle and Dynamic Balance in Football Players

Abstract: Background. Developing lower extremity muscles in a proportional shape plays an important role of balanced body movement. It is believed that special development of muscles which provide multidirectional movements of ankle will contribute to the increase of balance ability, and this may significantly support the improvement of technical skill performance in football. The aim of the research was to examine the ability to keep dynamic balance and ankle joint muscle strength in football players, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Previous research noted significant differences in limb dominance [29] , this study demonstrated no significant difference between limbs on the CMAS score for both tasks (left; 4.8 ± 0.8 vs. right; 4.3 ± 0.7, p = 0.175). With 10 out of 11 participants right foot dominant, it is unclear what the impact limb dominance is on COD performance.…”
Section: Discussioncontrasting
confidence: 71%
“…Previous research noted significant differences in limb dominance [29] , this study demonstrated no significant difference between limbs on the CMAS score for both tasks (left; 4.8 ± 0.8 vs. right; 4.3 ± 0.7, p = 0.175). With 10 out of 11 participants right foot dominant, it is unclear what the impact limb dominance is on COD performance.…”
Section: Discussioncontrasting
confidence: 71%